2011
DOI: 10.3892/or.2011.1458
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of miR-27b in human glioma

Abstract: Abstract. Our previous miRNAs profiling study showed that miR-27b was up-regulated in glioma cells compared with H4 low grade astrocytoma cells. However, the main function of miR-27b in glioma in not known yet. The aim of this study was to investigate the expression and function of miR-27b in the pathogenesis of glioma. Real-time PCR showed that miR-27b was up-regulated in glioma samples and glioma cells. Downregulation of miR-27b triggered growth inhibition, induced apoptosis and inhibited invasion in glioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
(17 reference statements)
2
22
0
Order By: Relevance
“…MiR-23b has been reported to function as a renal cancer oncogene [25], similar to ovarian cancer seen in the present study, whereas it functions as a tumor suppressor in hepatocellular carcinoma [26]. The introduction of pre-miR-27b stimulates invasion in breast cancer cells by targeting the ST14 tumor suppressor [27], and is upregulated in glioma cells and tumor tissues [28]. However, it is downregulated in lung cancer tissue [29].…”
Section: Discussionsupporting
confidence: 64%
“…MiR-23b has been reported to function as a renal cancer oncogene [25], similar to ovarian cancer seen in the present study, whereas it functions as a tumor suppressor in hepatocellular carcinoma [26]. The introduction of pre-miR-27b stimulates invasion in breast cancer cells by targeting the ST14 tumor suppressor [27], and is upregulated in glioma cells and tumor tissues [28]. However, it is downregulated in lung cancer tissue [29].…”
Section: Discussionsupporting
confidence: 64%
“…miRNA expression alterations have been reported to be involved in several physiological and pathological processes such as aging, tumorigenesis, metabolism and inflammation, 8 , 49 , 50 , 51 and several studies have demonstrated differential expression of miR-27 in various diseases. miR-27 is upregulated in breast cancer, oral cancer, glioma and peripheral arterial disease 41 , 52 , 53 , 54 , 55 and is downregulated in prostate cancer and head and neck squamous cancer. 56 , 57 Several reports have shown that mitochondrial fusion can inhibit cell death, whereas mitochondrial fission is involved in the promotion of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 It has reported that marked downregulation of miRNA-27b-3p in tamoxifen-resistant cells compared with parental MCF-7 cells. 14 Recently, several studies have identified miR-27b-3p (also known as miR-27b) promotes cell proliferation and invasion in glioma and breast cancer, 15, 16 and blocks paclitaxel-induced apoptosis in cervical cancer. 17 MiR-27b-3p also reportedly plays a cancer-promoting role and is associated with poor prognosis in triple-negative breast cancer patients.…”
mentioning
confidence: 99%